(untitled) (Medico Legal Update, 2020)
One of the most world anti parasitic and antibacterial compound used is Metronidazole (MTZ),all Drug toxicity must be acceptable to relief patients and should cause less harm to human than infection itself. MTZ is potentially genotoxic to humans due to the following facts: it is a proven toxogenic to human cells as well as wide range of side effects including chromosomal aberration and reproductive toxicity. The study is designed to assess the cytotoxic and reproductive toxicity effects of two dose of MTZ (250 mg/kg b.wt group and 500 mg/kg b.wt group) orally by gavage for 30 days and compared with control group (given normal saline) and then examine chromosomes from bone marrow cells and testicular gametogenic activity of adult male albino rats. Evident toxicity of both treatments of MTZ groups on chromosomal aberration (fragment, deletion and ring chromosome),with increased number of polyploid cells which were significantly increased (P< 0.05) by dose and time compared with control group. MTZ significant decrease in sperm activity and in deformed form (P< 0.05) .as well as reduced testes weight, also MTZ stimulate injured in seminiferous tubules especialy germinal epithelium.